Progression-free survival estimation of docetaxel-based second-line treatment for advanced non-small cell lung cancer: a pooled analysis from 18 randomized control trials - N, Chaithra; Jain, Anisha; C, Sahana; Shreevatsa, Bhargav; Rajendrasozhan, Saravanan; Dharmashekar, Chandan; Suresh, Kuralayanapalya Puttahonnappa; Patil, Sharanagouda S.; Singh, Pranav; Vishwanath, Prashant; Srinivasa, Chandrashekar; Kollur, Shiva Prasad; et al. (Frontiers in Oncology, 2024)
Background: Lung cancer is the foremost cause of cancer-related death globally, with non-small cell lung cancer (NSCLC) accounting for 85-90% of cases. Targeted therapy is the most essential therapeutic option for NSCLC, other common treatments include radiation therapy, surgery, chemotherapy, and immunotherapy. Objective: Our study objective was to estimate whether progression-free survival (PFS) is an outcome of NSCLC extracted from 18 randomized control trials (RCTs) with docetaxel as experimental group and antineoplastic agent, kinase inhibitor, and monoclonal antibodies as a control group. Methods: We selected relevant studies published between 2011 and 2022 using Google Scholar, PubMed, Scopus, Science Direct, and Cochrane Library. Advanced NSCLC, chemotherapy, RCT, docetaxel, and second-line treatment were the terms included in the search. A total of 9738 patients were evaluated from the 18 identified studies. We used the meta package of R Studio to perform the meta-analysis. Graphical funnel plots were used to evaluate publication bias visually. Results: Patients who underwent docetaxel-based therapy had a considerably longer PFS than those who got antineoplastic agents, kinase inhibitors, or monoclonal antibodies-based treatment. Patients in the standard treatment arm had a slightly longer PFS than those in the experimental therapy arm in the overall meta-analysis. Conclusion: Docetaxel outperformed monoclonal antibodies, antineoplastic agents, and kinase inhibitors in the second-line therapy of advanced NSCLC since PFS was extensively utilized.